SELECTION OF ROUND EGGPLANT BASED ON COLOR AND SIZE BASED ON ARDUINO - Rahady , Redwin Arie; Ayuni , Shazana Dhiya (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Eating vegetables is important for both humans and farmers who process them to meet consumer needs. Round eggplant is a popular vegetable because it maintains its high nutritional value even with minimal cooking, leading to increased demand. A system for sorting eggplants based on color and size using Arduino Mega is needed. The research method used is research and development to test sensor accuracy and tool reliability in accordance with the research objectives. The tool uses Arduino Mega as a microcontroller, TCS3200 sensor for eggplant color detection, and HC-SR04 sensor for object detection. During the separation process, the eggplant rounds will be moved by a conveyor using a DC motor. In the last step, the tool will direct the round eggplant into the container based on its color and size using a servo motor